PENGARUH LIQUIDITY, LEVERAGE, ASSET TANGIBILITY, BOARD SIZE DAN FIRM AGE TERHADAP PROFITABILITY - Chang, Michelle; Sufiyati, Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this research is to indetify and analyze about the effect of liquidity, leverage, asset tangibility, board size and firm age on profitability in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2017-2020 period. The research design is a descriptive study with a purposive sampling method which resulted 284 research samples. The data processing technique uses multiple regression analysis using Eviews 10 software. The results showed that the liquidity and leverage don’t have a positive effect on profitability. Asset tangibility and board size don’t have a negative effect on profitability. While the firm age has a negative effect on profitability. The implication of this research is that resource management, responsiveness to the market and the ability to analyze factors that affect profitability can increase the profitability and performance of the company so as to meet the needs of stakeholders and maintain survival.